Emergency Fostering of Dogs From Animal Shelters During the COVID-19 Pandemic: Shelter Practices, Foster Caregiver Engagement, and Dog Outcomes - Gunter, Lisa M.; Gilchrist, Rachel J.; Blade, Emily M.; Reed, Jenifer L.; Isernia, Lindsay T.; Barber, Rebecca T.; Foster, Amanda M.; Feuerbacher, Erica N.; Wynne, Clive D. L. (Frontiers in Veterinary Science, 2022)
Each year, millions of dogs enter thousands of animal shelters across the United States. Life in the shelter can be stressful, and one type of intervention that improves dogs’ experience is human interaction, particularly stays in foster homes. Prior research has demonstrated that fostering can reduce dogs’ cortisol and increase their resting activity. Despite these benefits, little is understood about the utilization of foster caregiving in animal shelters, and even less so during a crisis. On March 11, 2020, the World Health Organization deemed the coronavirus outbreak a worldwide pandemic, and subsequently a nationwide emergency was declared in the United States. Nearly all states issued stay-at-home orders to curb the spread of the virus. During this time, media outlets reported increased interest in the adoption and fostering of shelter pets. This study explores canine foster caregiving at 19 US animal shelters during the first four months of the COVID-19 pandemic. In our investigation, we found that shelters’ utilization of foster caregiving increased from March to April 2020 but returned to initial pandemic levels by June 2020. Slightly less than one-half of foster caregivers were community members with no prior relationship with the shelter, and these caregivers were over four times more likely to adopt their fostered dogs than those with a pre-existing relationship to the shelter. Individuals fostering with the intention to adopt, in fact, adopted their dogs in nearly three-quarters of those instances. With regards to shelters’ available resources, we found that low- and very low-resource shelters relied more heavily on individuals with prior relationships to provide foster caregiving while very high-resource shelters more often recruited new community members. We also found that our lowest resourced shelters transferred more dogs out of their facilities while more resourced shelters rehomed dogs directly to adopters. To our knowledge, these findings represent the first in-depth reporting about dog fostering in US animal shelters and, more specifically, foster caregiving during the COVID-19 pandemic. In total, they provide greater understanding of how monetary and human resources were utilized to affect the care and ultimately, the outcomes of shelter dogs during this time.